Effects of downstream entry in a supply chain with a spot market. (3rd October 2019) - Xing, Wei; Zhang, Qi; Zhao, Xuan; Liu, Liming
Abstract: This article contributes to research at the interface of marketing, operations, and risk management by investigating the effects of downstream entry in a two-echelon supply chain with risk-averse supply chain members and a liquid spot market for trading intermediate goods. We find that at downstream entry, the upstream supplier may decrease the contract price of the intermediate goods to balance its risk-free utility from the contract channel and its risky utility from the spot market; correspondingly, downstream manufacturers may increase their contract quantities. As a result, downstream entry may hurt the supplier and benefit the incumbent manufacturers. We also identify situations where downstream entry can lead to a "win-win-win" situation, where the supplier, incumbent manufacturers, and final product consumers all benefit from downstream entry. Furthermore, when spot price volatility is high, the supplier may engage in speculative trading, but downstream entry discourages this speculative behavior. We conclude that these results are driven by the combined effects of spot trading and the risk attitudes of supply chain members. Specifically, the effects of downstream entry are dramatically affected by the risk attitude of manufacturers, but only slightly affected by that of the supplier. Finally, we find that the main results hold when the supplier's capacity level is endogenous.